Public Emergency, Presidentialism and Rule of Law in Argentina in the context of the COVID-19 - Altavilla, Cristian (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The pandemic generated by the COVID-19 activated the institutional levers included in the Argentine Constitution to face public emergencies. However, the magnitude and impact of the situation generated by the COVID-19 pandemic surpassed and exceeded any legal and/or constitutional provision. The health emergency highlighted a series of problems, social, political and economic, as well as issues related to the institutional design of the Argentine constitutional system. The aim of this paper is to analyzethe role of the Argentine State powers in this extraordinary situation of public health emergency and their performance in it, through a critical look at their performance, in order to examine whether it has beendeveloped within the framework of legality established by the constitutional regime, or whether it has been outside such legality.  The Argentine Republic shares with its Latin American sister nations the phenomenon known as "hyperpresidentialism", manifested in the great number of powers (de facto and de jure)exercised by the President of the Nation, as the person in charge of the executive power, creating a situation that ends up generating a dangerous imbalance of powers that threatens the democratic and republican system. The pandemic, in this sense, only highlighted this anomaly of the constitutional system.